Construction and Validation of the Career and Educational Decision Self-Efficacy Inventory for Secondary Students (CEDSIS). (March 2018) - Ho, Esther Sui Chu; Sum, Kwok Wing
This study aims to construct and validate the Career and Educational Decision Self-Efficacy Inventory for Secondary Students (CEDSIS) by using a sample of 2, 631 students in Hong Kong. Principal component analysis yielded a three-factor structure, which demonstrated good model fit in confirmatory factor analysis. High reliability was found for the whole scale and each subscale, and construct validity was exhibited by the positive correlations with general self-esteem. Overall, evidence indicates that CEDSIS is a valid and reliable tool for effectively and efficiently assessing the educational and career decision-making self-efficacy of secondary students. Finally, implications and limitations of this study are discussed.